Aspek – Aspek Penting Membangun Kehidupan di Desa Menuju Kesejahteraan dan Keadilan Sosial - Abustan (Universitas Muhammadiyah Malang, 2022)
Development in the village is an integral part of national development based on Pancasila and the Constitution of the Republic of Indonesia of 1945, implemented to realize equitable development throughout Indonesia which is not only concentrated in the city, but also in remote villages where the majority of the population actually lives in the interior. The dynamics of development infrastructure have recently moved to the village as a manifestation of the realization of a prosperous, socially just, and equitable society. Of course, it is not limited to material development but also spiritual. This research takes the subject of discussion about the aspects that concern the government in the implementation of village development in realizing welfare and social justice. The purpose of the research is to find out the aspects that concern the government in the implementation of village development in realizing welfare and social justice. This research is empirical research that uses a sociological juridical approach. The reality of the conditions in the village, in the research, conducted found various advances that exist, both in the sector of education of the reflective school infrastructure, health facilities were people for treatment (Posyandu and Puskesmas), and people's activities equipped with information technology with digitalization systems (Wifi). That is the development of development progress found from the research conducted. Abstrak Pembangunan di desa merupakan bagian integral dari pembangunan nasional berdasarkan Pancasila dan Undang-undang Dasar Negara Republik Indonesia Tahun 1945, dilaksanakan untuk mewujudkan pemerataan pembangunan seluruh Indonesian yang tidak hanya terpusat (terkonsentrasi) di kota, tetapi juga di pelosok desa yang mayoritas penduduk kenyataannya bermukim di pedalaman. Dinamika infrastruktur pembangunan akhir-akhir ini bergerak ke desa sebagai manifestasi dari perwujudan masyarakat sejahtera, berkeadilan sosial, dan merata. Tentu saja, tidak sebatas pembangunan materiil namun juga spiritual. Penelitian ini mengambil pokok bahasan tentang aspek-aspek yang menjadi perhatian pemerintah dalam implementasi pembangunan desa dalam mewujudkan kesejahteraan dan keadilan sosial. Tujuan penelitian untuk mengetahui aspek-aspek yang menjadi perhatian pemerintah dalam implementasi pembangunan desa dalam mewujudkan kesejahteraan dan keadilan sosial. Penelitian ini merupakan penelitian empiris yang menggunakan pendekatan yuridis sosiologis. Realitas kondisi yang ada di desa, dalam penelitian yang dilakukan ditemukan berbagai kemajuan yang ada, baik di sektor pendidikan infrastruktur sekolah yang refresentatif, sarana kesehatan tempat masyaraka untuk berobat (Posyandu dan Puskesmas) serta aktifitas rakyat yang dilengkapi tehnologi informasi dengan sistem digitalisasi (Wifi). Itulah perkembangan kemajuan pembangunan yang ditemukan dari riset yang dilakukan.